2011
DOI: 10.1109/tec.2010.2088400
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Hysteresis and Magnetic Couplings on the Stability Domain of Ferroresonance in Asymmetric Three-Phase Three-Leg Transformers

Abstract: This paper investigates the stability domain of ferroresonance in asymmetric three-phase three-leg transformers considering magnetic couplings and hysteresis effects of the core. A newly developed and accurate time-domain transformer model capable of simulating dynamic and transient operating conditions is implemented in this study. The model is based on electromagnetic circuit theory and considers dynamic hysteresis effects (major and minor loops) as well as core topology, asymmetry, and magnetic flux cross-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 47 publications
0
40
0
Order By: Relevance
“…In this equivalent circuit, the resistor R models the potential transformer (PT) core losses. The core losses can be modelled by either accurate hysteresis model or a constant linear resistance [28][29][30]. The magnetisation current is modelled by a two-term polynomial, which has been obtained and introduced in [27], and given in (1).…”
Section: Distribution Network Modellingmentioning
confidence: 99%
“…In this equivalent circuit, the resistor R models the potential transformer (PT) core losses. The core losses can be modelled by either accurate hysteresis model or a constant linear resistance [28][29][30]. The magnetisation current is modelled by a two-term polynomial, which has been obtained and introduced in [27], and given in (1).…”
Section: Distribution Network Modellingmentioning
confidence: 99%
“…Multiple factors influence the occurrence of ferroresonance in an electric circuit; there are three critical components in an electrical circuit that must be present for ferroresonance to occur: 1) a nonlinear inductance [3]; 2) a capacitor [4];…”
Section: Ferroresonance After Islanding Of Synchronousmentioning
confidence: 99%
“…Multiple periodic and nonperiodic modes in the system can be initiated by ferroresonance [8]- [11]. Depending on the system parameters and the initial conditions in a ferroresonance circuit, fundamental [3], subharmonic [12], quasi-periodic [13], or chaotic [14] ferroresonance can occur.…”
Section: Ferroresonance After Islanding Of Synchronousmentioning
confidence: 99%
“…Using the method of Krylov and Bogoliubov from [30] and Migulin [31,32], and taking the first and second derivatives of the equation (21) and substituting it into equation (20), it can be shown that:…”
Section: Power System Modelingmentioning
confidence: 99%
“…The suppression technique of the ferroresonance phenomenon in the coupling capacitor of the voltage transformer has been given in [20]. The impact of hysteresis and magnetic couplings on the stability domain of ferroresonance in asymmetric three-phase three-leg transformers has been discussed in [21]. Mitigating the ferroresonance of 161 kV electromagnetic potential transformers by damping reactors in gas-insulated switchgear has been presented in [22].…”
Section: Introductionmentioning
confidence: 99%